Air‐Sea Interactions in the Cold Wakes of Tropical Cyclones - Claudia Pasquero; Fabien Desbiolles; Agostino N. Meroni (Geophysical Research Letters)
Abstract Tropical cyclones generate a large and wide cold wake along their trajectories, which conditions the subsequent evolution of the tropical cyclone themselves. The cold wakes persist for weeks, impacting both the upper ocean, the air‐sea fluxes, and the atmosphere. The study by Z. Ma et al. (2020, https://doi.org/10.1029/2020GL088873) for the first time analyzes a composite of remotely sensed data sets to show that cold wakes modify surface winds and reduce cloud coverage and rainfall. These results contribute to shedding light on the mechanisms at the origin of the air‐sea feedbacks, which can differ at different latitudes depending on the stability of the marine atmospheric boundary layer. The work stimulates further research to assess whether the cloud cover anomalies induced by tropical cyclones significantly modify the radiative budget of the Earth.